Keberadaan Residu Tetrasiklin pada Daging Ayam Broiler di Kabupaten Kudus (Studi di Pasar Tradisional dan Pasar Modern Tahun 2019) - Sabilla Ananda Aulia; Dwi Sutiningsih; Henry Setyawan; Ari Udiyono (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: One of the causes of antibiotic resistance is the presence of antibiotic residues in livestock, one of which is broiler chicken meat. Excessive use of antibiotics and not in accordance with the diagnosis will result in the discovery of antibiotic residue content in chicken meat and will endanger public health. The purpose of this study was to determine the description of the antibiotic residues of tetracycline in broiler chicken meat sold in traditional and modern markets in Jati District, Kudus Regency.Methods: This type of research is a descriptive observational study with a cross-sectional approach. The samples in this study were all broiler chicken meat sold in traditional markets (Bitingan Market, Sunggingan Ploso Market, and Baru Market) and in the modern Hypermart market with a total sample of 78 samples of broiler chicken meat taken with total population sampling technique. Sample testing was carried out at Balai Veteriner Boyolali using the Bioassay method.Result: Based on the results of the study, there is no tetracycline antibiotic residues were found in 78 (100%) broiler chicken meats sold in the Bitingan Market, Sunggingan Ploso Market, Baru Market, and Hypermart.Conclusion : There is no tetracycline antibiotic residues were found in broiler chicken meat sold in the Bitingan Market, Sunggingan Ploso Market, Baru Market, and Hypermart.